2001
DOI: 10.1038/sj.onc.1204319
|View full text |Cite
|
Sign up to set email alerts
|

DNA microarrays identification of primary and secondary target genes regulated by p53

Abstract: The transcriptional program regulated by the tumor suppressor p53 was analysed using oligonucleotide microarrays. A human lung cancer cell line that expresses the temperature sensitive murine p53 was utilized to quantitate mRNA levels of various genes at dierent time points after shifting the temperature to 328C. Inhibition of protein synthesis by cycloheximide (CHX) was used to distinguish between primary and secondary target genes regulated by p53. In the absence of CHX, 259 and 125 genes were up or down-reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
242
2
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(255 citation statements)
references
References 30 publications
10
242
2
1
Order By: Relevance
“…3A, top panels, compare lanes 3 and 4 and lanes 7 and 8, respectively). Some genes such as tumor necrosis factor receptor superfamily, member 10D (TNFRSF10D), sestrin 2 (SESN2), and BTG family member 2 (BTG2) are known to be induced by a genotoxic stress through a p53-dependent pathway [28] and both our micro-array analysis and our real-time PCR experiments indeed confirmed that these genes were induced upon 2 h of daunomycin treatment in HCT116 cells (Fig. 3B, on the left).…”
Section: Ikap/help1 Depletion Modulates Gene Expression In a Cell-typsupporting
confidence: 67%
“…3A, top panels, compare lanes 3 and 4 and lanes 7 and 8, respectively). Some genes such as tumor necrosis factor receptor superfamily, member 10D (TNFRSF10D), sestrin 2 (SESN2), and BTG family member 2 (BTG2) are known to be induced by a genotoxic stress through a p53-dependent pathway [28] and both our micro-array analysis and our real-time PCR experiments indeed confirmed that these genes were induced upon 2 h of daunomycin treatment in HCT116 cells (Fig. 3B, on the left).…”
Section: Ikap/help1 Depletion Modulates Gene Expression In a Cell-typsupporting
confidence: 67%
“…The p53 gene is a transcriptional regulator and transactivator of a growing number of specific genes implicated in the regulation of cell cycle and apoptosis. 3,36 Mutations in the p53 gene can be detected in up to 50% of various cancer entities. 37 A considerable number of studies have been performed with regard to the p53 status and its correlation to prognosis or therapeutical response in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These include Bax, a pro-apoptotic Bcl-2 family member (Miyashita et al, 1994), several mitochondrial proteins, Noxa, (Oda et al, 2000a), p53AIP1 (p53-regulated-apoptosis-inducing protein 1) (Oda et al, 2000b), and PUMA (p53-upregulated modulator of apoptosis) (Nakano and Vousden, 2001;Yu et al, 2001), and several genes associated with death receptor-mediated apoptosis, Fas, Killer/DR5, and PIDD (Lin et al, 2000;Wu et al, 2000). There does not appear to be a single gene that is the principal mediator of p53-induced apoptosis, but rather the response involves the activation of several apoptotic genes (Sionov and Haupt, 1999;Ryan et al, 2000;Kannan et al, 2001). In addition, there is much overlap in the pattern of genes regulated by p53 whether it results in growth arrest or apoptosis.…”
Section: P53 Signalingmentioning
confidence: 99%